Synthesis of nucleoside-boronic esters hydrophobic pro-drugs: a possible route to improve hydrophilic nucleoside drug loading into polymer nanoparticles - Abo-zeid, Yasmin; Mantovani, Giuseppe; Irving, William L.; Garnett, Martin.C (Elsevier, 2018)
Nucleoside analogues are active therapeutic agents for different types of diseases e.g. Cancer and virus infections. However, they are associated with several side effects due to off-target accumulation. Particulate delivery systems such as nanoparticles (NP) may be able to selectively target drug into affected organs and lower or omit off-target accumulation. Hydrophilic nucleoside analogues are poorly incorporated into NP. This work has used boronic compounds to synthesize more hydrophobic biodegradable pro-drugs of hydrophilic nucleosides to improve drug loading into NP. Ribavirin (RV) was used as a model hydrophilic nucleoside to test our hypothesis. RV is a broad antiviral agent, active against both RNA and DNA viruses. RV accumulates into Red Blood Cells (RBCs) causing haemolytic anaemia that restricts its therapeutic benefits. RBCs are reported to have no endocytic mechanisms. So, NP delivery should be advantageous. Two hydrophobic pro-drugs of RV were synthesized namely, ribavirin conjugated to phenylboronic acid and ribavirin conjugated to 4-butoxy-3, 5-dimethylphenylboronic acid and were encapsulated into polymer NP. It was shown that the pro-drugs were incorporated more effectively into polymer nanoparticles with a 1700 fold improved RV loading. Polymer NP had been prepared with biocompatible and biodegradable polymers, Poly(glycerol adipate) and its more hydrophobic derivatives.